Lectotype designations and taxonomic corrections on species of Lygaeoidea (Hemiptera: Heteroptera) described by Gustav Breddin - Kondorosy, Előd; Rédei, Dávid (Zootaxa, 2015)
Types of selected species of Lygaeoidea (Hemiptera: Heteroptera) described by Gustav Breddin, so far of unknown depository, were re-examined and the taxonomic and nomenclatural problems that existed among those species are discussed and resolved as required. The holotype of Dieuches schultheissi Breddin, 1906 is documented. Lectotypes are designated and documented for the following taxa: Lygaeidae: Aethalotus horni Breddin, 1907; Aspilogeton nubicola Breddin, 1901; Lygaeus hospes Fabricius, 1794 var. celebensis Breddin, 1901; Oxycarenidae: Oxycarenus musculus Breddin, 1907; Rhyparochromidae: Lispochroa blandula Breddin, 1907; Notochilaster teres Breddin, 1907; Dieuches horni Breddin, 1906; D. jacobsoni Breddin, 1906; D. nudipes Breddin, 1906; D. villosulus Breddin, 1906; Poeantius brevicollis Breddin, 1907; Pamera recincta Breddin, 1901; Paromius robustior Breddin, 1907. The following taxonomic changes are proposed: Naphius schultzei (Breddin, 1913), new combination (transferred from Rhyparochromus); Graptostethus verticalis (Dallas, 1852) = Pyrrhobaphus scutellatus Breddin, 1907, new subjective synonym; Naphius schultzei (Breddin, 1913) = Naphius capensis Scudder, 1971, new subjective synonym.